A multi-band self-recovering stress luminescent material and its preparation method and application
By adopting the chemical structure of MaP2O7:Rb and the high-temperature calcination preparation method, the problem that existing rare earth-doped luminescent materials need to be excitated before they can emit light is solved, and multi-band stress luminescence without excitation under the action of mechanical force is achieved, which improves the luminescence intensity and Easy to prepare, suitable for a variety of applications.
Patent Information
- Application Number
- CN202411423560.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-12
AI Technical Summary
The existing rare earth-doped M2P2O7 luminescent materials need to be excitated by ultraviolet or visible light in advance to emit light, and the luminescent intensity is not strong, the preparation method is complex, and the application range is limited.
The chemical expression of the multi-band self-recovering stress luminescent material is MaP2O7:Rb, where M is at least one element of Mg, Ca, Sr, and Zn, P is a phosphorus element, O is an oxygen element, and R is selected from Eu, At least one element of Tb, Dy, Mn, Sm, Bi is prepared by high-temperature calcination and pulverization preparation method to produce a self-recoverable stress-emitting material that emits light without ultraviolet light or visible light excitation.
It realizes a multi-band stress luminescent material that emits light without preexcitation under mechanical force. It has stable physical and chemical properties, simple process and low cost. It is suitable for various stress sensing and display applications.
Smart Images

Figure CN118931534B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of inorganic luminescent materials, and in particular to a stress luminescent material and a preparation method and application thereof. Background Art
[0002] Mechanoluminescence refers to the phenomenon that when an object is subjected to external stress, it converts mechanical energy into photons and releases energy to the outside. Mechanoluminescence material is a material that can release photons simply by applying mechanical stimulation to the material. These mechanical stimulations include: compression, twisting, friction, impact, stretching, cutting, etc. Based on mechanical stimulation, stress luminescence can be divided into three categories: elastic stress luminescence, plastic stress luminescence and fracture luminescence. Elastic stress luminescence materials are repeatable. Within the elastic limit of the material, the stress luminescence intensity is positively correlated with the mechanical force it is subjected to. Based on whether it is recoverable, stress luminescence materials are divided into recoverable stress luminescence materials and irrecoverable stress luminescence materials. Currently, many types of stress luminescence materials have been developed, including ZnS:Mn 2+ ,ZnAl2O4:Mn 2+ ,SrAl2O4:Eu 2+ ,SrCaMgSi2O7:Eu 2+ , Ca2Al2Si2O7:Eu 2+ and CaZnOS:Mn 2+ However, the types of stress luminescent materials with practical application value are very limited, limited to SrAl2O4:Eu 2+ , ZnS:Cu and so on.
[0003] Rare earth doped M2P2O7 (M=Ca, Sr, Mg, Zn) luminescent materials have a relatively broad application prospect due to their relatively low raw material cost and their ability to be used as high concentration doping matrix. In addition, compared with the current sulfide materials, their physical and chemical properties are very stable, non-toxic, and the synthesis method is simple. However, there are the following problems with such luminescent materials in the prior art: first, such luminescent materials need to be excited by ultraviolet light or visible light in advance to emit light (such as Jia Xiaohui. Preparation and performance of rare earth doped lanthanum trimetaphosphate and pyrophosphate luminescent materials [D]. Guizhou Normal University, 2015.), and the luminescent intensity is not strong. Second, the preparation method is complicated. Summary of the invention
[0004] The present application proposes a multi-band self-recovering stress luminescent material and its preparation method and application, aiming to provide a self-recovering stress luminescent material with a simple preparation process, which can emit light without ultraviolet light or visible light and irradiation, and whose luminescent band can be adjusted.
[0005] The technical solution adopted by the invention is: a multi-band self-recovering stress luminescent material, the chemical formula of which is: M a P2O7:R b , wherein M is at least one element selected from Mg, Ca, Sr, and Zn; P is phosphorus; O is oxygen; R is at least one element selected from Eu, Tb, Dy, Mn, Sm, and Bi; a and b are molar coefficients, and 1.5≤a<2, 0.001≤b≤0.5, and a+b=2.
[0006] Furthermore, the M contains Ca and at least one element of Mg, Sr, and Zn.
[0007] Preferably, the chemical expression of the restorable stress luminescent material is Ca 1.984 P2O7:Dy 0.016 .
[0008] Preferably, the chemical expression of the restorable stress luminescent material is Ca 1.988 P2O7:Eu 0.012 .
[0009] Preferably, the chemical expression of the restorable stress luminescent material is Ca 1.988 P2O7:Tb 0.012 .
[0010] Preferably, the chemical expression of the restorable stress luminescent material is Ca 1.976 Zn 0.01 P2O7:Mn 0.014 .
[0011] Preferably, the chemical expression of the restorable stress luminescent material is Ca 1.98 Mg 0.01 P2O7:Sm 0.01 .
[0012] Preferably, the chemical expression of the restorable stress luminescent material is Ca 1.976 Sr 0.01 P2O7:Bi 0.014 .
[0013] A method for preparing a multi-band self-recovering stress luminescent material, the preparation method comprising the following steps:
[0014] (1) High-purity carbonate and / or acetate and / or oxide containing M, ammonium hydrogen phosphate or ammonium dihydrogen phosphate, and oxide and / or boride and / or carbonate containing R are used as raw materials, and flux is added, and the mixture is ground uniformly;
[0015] (2) calcining the mixture obtained in step (1) at a high temperature in air or N2 / H2 atmosphere, wherein the calcination conditions are: heating to 500°C at a heating rate of 5-10°C / min and keeping the temperature for 1-2 hours, then heating to 1100-1300°C and calcining for 6-20 hours, and calcining at least once;
[0016] (3) The calcined product obtained in step (2) is cooled, crushed and sieved to obtain the restorable stress luminescent material.
[0017] Furthermore, the flux is ammonium chloride, and the flux accounts for 0.1%-5% of the total mass of the raw materials.
[0018] The present invention also proposes an application of a multi-band self-recovering stress luminescent material in preparing an elastic composite stress luminescent body.
[0019] Compared with the prior art, the present invention proposes a stress-induced multi-band stress luminescent material within the visible light range and a preparation method. Compared with most existing stress luminescent materials, it does not require pre-irradiation with ultraviolet light or visible light, and can emit light under a certain mechanical force. The multi-band stress luminescent material proposed in the present invention can be compounded with materials such as PDMS and PET, and the stress luminescence intensity of the formed elastomer is basically linearly related to the mechanical force, and the self-recovery property is relatively good. The matrix material in the present invention has stable physical and chemical properties, simple process, low equipment requirements, easy to control reaction conditions, low cost, no toxic and harmful substances are produced in the preparation process, and it is environmentally friendly. It has potential applications in various visual stress sensing, stress displays and biological stress sensing detection. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0021] Figure 1 The X-ray powder diffraction spectra of the self-recovering stress luminescent materials of Examples 1 to 6 of the present invention are shown.
[0022] Figure 2 This is a stress emission spectrum diagram of the self-recovering stress luminescent material according to Example 1 of the present invention.
[0023] Figure 3 This is a stress luminescence photograph of the self-recovering stress luminescent material during the grinding process according to Example 1 of the present invention.
[0024] Figure 4This is a stress luminescence photograph of the PDMS elastomer under mechanical compression used in the self-recovering stress luminescent material of Example 1 of the present invention.
[0025] Figure 5 This is a linear relationship graph of the stress luminescence intensity of the PDMS elastomer used in the self-recovering stress luminescent material of Example 1 of the present invention under different mechanical force changes.
[0026] Figure 6 This is a relationship graph of the self-recovery stress luminescence intensity of the PDMS elastomer used in the self-recovery stress luminescent material of Example 1 of the present invention.
[0027] Figure 7 This is a stress emission spectrum diagram of the self-recovering stress luminescent material according to the second embodiment of the present invention.
[0028] Figure 8 This is a stress luminescence photograph of the PDMS elastomer under mechanical compression used in the self-recovering stress luminescent material of Example 2 of the present invention.
[0029] Fig. 9 This is a linear relationship graph of the stress luminescence intensity of the PDMS elastomer used in the self-recovering stress luminescent material of Example 2 of the present invention under different changes in mechanical force.
[0030] Fig.10 This is a relationship graph of the self-recovery stress luminescence intensity of the PDMS elastomer used in the self-recovery stress luminescent material of Example 2 of the present invention.
[0031] Fig.11 This is a stress emission spectrum diagram of the self-recovering stress luminescent material according to the third embodiment of the present invention.
[0032] Fig.12 This is a stress luminescence photograph of the self-recovering stress luminescent material during the grinding process according to Example 3 of the present invention.
[0033] Fig.13 This is a stress luminescence photograph of the PDMS elastomer under mechanical compression used in the self-recovering stress luminescent material of Example 3 of the present invention.
[0034] Fig.14 This is a linear relationship graph of the stress luminescence intensity of the PDMS elastomer used in the self-recovering stress luminescent material of Example 3 of the present invention under different changes in mechanical force.
[0035] Fig.15 This is a relationship graph of the self-recovery stress luminescence intensity of the PDMS elastomer used in the self-recovery stress luminescent material of Example 3 of the present invention.
[0036] Fig.16This is a stress emission spectrum diagram of the self-recovering stress luminescent material according to Example 4 of the present invention.
[0037] Fig.17 This is a stress luminescence photograph of the self-recovering stress luminescent material during the grinding process according to the fourth embodiment of the present invention.
[0038] Fig.18 This is a stress luminescence photograph of the PDMS elastomer under mechanical compression used in the self-recovering stress luminescent material of Example 4 of the present invention.
[0039] Fig.19 This is a linear relationship graph of the stress luminescence intensity of the PDMS elastomer used in the self-recovering stress luminescent material of Example 4 of the present invention under different changes in mechanical force.
[0040] Fig. 20 This is a relationship graph of the self-recovery stress luminescence intensity of the PDMS elastomer used in the self-recovery stress luminescent material of Example 4 of the present invention.
[0041] Fig.21 This is a stress emission spectrum diagram of the self-recovering stress luminescent material according to Example 5 of the present invention.
[0042] Fig. 22 This is a stress luminescence photograph of the self-recovering stress luminescent material during the grinding process according to Example 5 of the present invention.
[0043] Fig.23 This is a stress luminescence photograph of the PDMS elastomer under mechanical compression used in the self-recovering stress luminescent material of Example 5 of the present invention.
[0044] Fig.24 This is a linear relationship graph of the stress luminescence intensity of the PDMS elastomer used in the self-recovering stress luminescent material of Example 5 of the present invention under different changes in mechanical force.
[0045] Fig.25 This is a relationship graph of the self-recovery stress luminescence intensity of the PDMS elastomer used in the self-recovery stress luminescent material of Example 5 of the present invention.
[0046] Fig.26 This is a stress emission spectrum diagram of the self-recovering stress luminescent material according to Example 6 of the present invention.
[0047] Fig. 27 This is a stress luminescence photograph of the self-recovering stress luminescent material during the grinding process according to Example 6 of the present invention.
[0048] Fig.28 This is a stress luminescence photograph of the PDMS elastomer under mechanical compression used in the self-recovering stress luminescent material of Example 6 of the present invention.
[0049] Fig.29 This is a linear relationship graph of the stress luminescence intensity of the PDMS elastomer used in the self-recovering stress luminescent material of Example 6 of the present invention under different changes in mechanical force.
[0050] Fig.30 This is a relationship diagram of the self-recovery stress luminescence intensity of the PDMS elastomer used in the self-recovery stress luminescent material of Example 6 of the present invention.
[0051] Fig.31 The X-ray powder diffraction spectra of the self-recovering stress luminescent materials of the comparative example and the third embodiment of the present invention are shown.
[0052] Fig.32 It is a stress emission spectrum diagram of the self-recovering stress luminescent material of the comparative example and the third embodiment of the present invention. DETAILED DESCRIPTION
[0053] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0054] The present invention proposes a multi-band self-recovering stress luminescent material, the chemical expression of which is M a P2O7:R b , wherein M is at least one element selected from Mg, Ca, Sr, and Zn; P is phosphorus; O is oxygen; R is at least one element selected from Eu, Tb, Dy, Mn, Sm, and Bi; a and b are molar coefficients, 1.5≤a<2, 0.001≤b≤0.5, and a+b=2.
[0055] The preparation process of the recoverable stress luminescent material is as follows:
[0056] (1) High-purity carbonate and / or acetate and / or oxide containing M, ammonium hydrogen phosphate or ammonium dihydrogen phosphate, and oxide and / or boride and / or carbonate containing R are used as raw materials, and flux is added, and the mixture is ground uniformly;
[0057] (2) calcining the mixture obtained in step (1) at a high temperature in air or N2 / H2 atmosphere, wherein the calcination conditions are: heating to 500°C at a heating rate of 5-10°C / min and keeping the temperature for 1-2 hours, then heating to 1100-1300°C and calcining for 6-20 hours, and calcining at least once;
[0058] (3) The calcined product obtained in step (2) is cooled, crushed and sieved to obtain the restorable stress luminescent material.
[0059] The following will be introduced in conjunction with specific embodiments:
[0060] Embodiment 1
[0061] Weigh various raw materials CaCO3, (NH4)2HPO4, and Dy2O3 according to the chemical formula. Add NH4Cl as a flux and add it according to the flux accounting for 2% of the total mass of the total raw materials. The weighed molar number of Dy2O3 is 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, and 0.01, that is, the x value is 0.008, 0.01, 0.012, 0.014, 0.016, 0.018, and 0.02. After the above raw materials are fully ball-milled and mixed evenly. After the above raw materials are fully ball-milled and mixed evenly, they are loaded into a corundum crucible, heated to 500°C at a heating rate of 5-10°C / min, kept at 500°C for 1 hour in an air atmosphere, and then raised to 1300°C and kept for 8 hours. After the sintered body is cooled, it is crushed, sieved, and graded to obtain the chemical composition of Ca in the present invention. 2-x P2O7:Dy x Stress luminescent materials. 1.984 P2O7:Dy 0.016 The X-ray diffraction spectrum of Figure 1 The emission spectrum is shown in Figure 2 As shown, the strongest emission wavelength is at 570nm for yellow light. The stress luminescence of the powder during the grinding process is as follows Figure 3 shown.
[0062] In the application of the first embodiment, Ca 2-x P2O7:Dy x The fluorescent material is combined with polydimethylsiloxane (PDMS) to form an elastic film: first, the fluorescent material, PDMS and curing agent are mixed in a ratio of 1:1:0.1, and then the mixed slurry is poured into a pre-cleaned mold, and finally it is placed in a vacuum oven and cured at 80°C for 2 hours to obtain an elastomer containing stress-luminescent material. Figure 4 Contains Ca 1.984 P2O7:Dy 0.016 The luminescence photo of the elastomer of fluorescent material under extrusion stress shows that the emission of green light can be clearly observed. The linear relationship between stress luminescence and mechanical force is as follows Figure 5 As shown, the self-healing characteristics are as follows Figure 6 shown.
[0063] Embodiment 2
[0064] Weigh various raw materials CaCO3, (NH4)2HPO4, and Eu2O3 according to the chemical formula. Add NH4Cl as a flux and add it according to the flux accounting for 0.1% of the total mass of the total raw materials. The weighed molar number of Eu2O3 is 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, and 0.01, that is, the x value is 0.008, 0.01, 0.012, 0.014, 0.016, 0.018, and 0.02. After the above raw materials are fully ball-milled and mixed evenly, they are loaded into a corundum crucible, heated to 500°C at a heating rate of 5-10°C / min, and kept at 500°C for 1 hour under N2 / H2 atmosphere. The temperature is raised to 1200°C and kept for 8 hours. After the sintered body is cooled, it is crushed, sieved, and classified to obtain the chemical composition of Ca in the present invention. 2-x P2O7:Eu x The prepared stress luminescent material has the chemical formula of Ca 1.988 P2O7:Eu 0.012 The X-ray diffraction spectrum of Figure 1 As shown, the stress emission spectrum is Figure 7 As shown, the strongest emission wavelengths are at 414 nm for blue light and 612 nm for red light.
[0065] In the application of the second embodiment, Ca 2-x P2O7:Eu x The fluorescent material is combined with polydimethylsiloxane (PDMS) to form an elastic film: first, the fluorescent material, PDMS and curing agent are mixed in a ratio of 1:1:0.1, and then the mixed slurry is poured into a pre-cleaned mold, and finally it is placed in a vacuum oven and cured at 80°C for 2 hours to obtain an elastomer containing stress-luminescent material. Figure 8 Contains Ca 1.988 P2O7:Eu 0.012 The luminescence photo of the elastomer of fluorescent material under extrusion stress shows that the emission of blue and red light can be clearly observed. The linear relationship between stress luminescence and the mechanical force is as follows: Fig. 9 As shown, the self-healing characteristics are as follows Fig.10 shown.
[0066] Embodiment 3
[0067] Weigh various raw materials CaCO3, (NH4)2HPO4, and Tb4O7 according to the chemical formula. Add NH4Cl as a flux and add it according to the flux accounting for 1% of the total mass of the total raw materials. The weighed molar number of Tb4O7 is 0.002, 0.0025, 0.003, 0.004, 0.005, 0.006, and 0.007, that is, the value of x is 0.008, 0.01, 0.012, 0.016, 0.02, 0.024, and 0.028. After the above raw materials are fully ball-milled and mixed evenly, they are loaded into a corundum crucible, and the temperature is raised to 500°C at a heating rate of 5-10°C / min. Keep it at 500°C for 1 hour in an air atmosphere, and then raise the temperature to 1100°C and keep it for 8 hours. After cooling the sintered body, crush, sieve, and classify it to obtain the chemical composition of Ca in the present invention. 2-x P2O7:Tb x The stress luminescent material prepared by Ca 1.988 P2O7:Tb 0.012 The X-ray diffraction spectrum of Figure 1 As shown, the stress emission spectrum is Fig.11 As shown in Figure 2, the strongest emission wavelength is at 541 nm in green light. The stress luminescence of the powder during the grinding process is shown in Figure 2. Fig.12 shown.
[0068] In the application of the third embodiment, Ca 2-x P2O7:Tb x The fluorescent material is combined with polydimethylsiloxane (PDMS) to form an elastic film: first, the fluorescent material, PDMS and curing agent are mixed in a ratio of 1:1:0.1, and then the mixed slurry is poured into a pre-cleaned mold, and finally it is placed in a vacuum oven and cured at 80°C for 2 hours to obtain an elastomer containing stress-luminescent material. Fig.13 Contains Ca 1.988 P2O7:Tb 0.012 The luminescence photo of the elastomer of fluorescent material under extrusion stress shows that the emission of green light can be clearly observed. The linear relationship between stress luminescence and mechanical force is as follows Fig.14 As shown, the self-healing characteristics are as follows Fig.15 shown.
[0069] Embodiment 4
[0070] Weigh various raw materials CaCO3, (CH3COO)2Zn, NH4H2PO4, and MnCO3 according to the chemical formula. NH4Cl is added as a flux at 3% of the mass of all raw materials, and the molar number of MnCO3 weighed is 0.08, 0.01, 0.012, 0.014, 0.016, 0.018, and 0.02, that is, the x value is 0.08, 0.01, 0.012, 0.014, 0.016, 0.018, and 0.02. After the above raw materials are fully ball-milled and mixed evenly, they are loaded into a corundum crucible, heated to 500°C at a heating rate of 5-10°C / min, and kept at 500°C for 1 hour in an air atmosphere. The temperature is raised to 1100°C and kept for 8 hours. After the sintered body is cooled, it is crushed, sieved, and classified to obtain the chemical composition of Ca in the present invention. 1.99-x Zn 0.01 P2O7:Mn x Stress luminescent materials. Among them, Ca 1.976 Zn 0.01 P2O7:Mn 0.014 The X-ray diffraction spectrum of Figure 1 The emission spectrum is shown in Fig.16 As shown in the figure, the strongest emission wavelength is at 566 nm in yellow light. The stress luminescence of the powder during the grinding process is shown in the figure. Fig.17 shown.
[0071] In the application of the fourth embodiment, Ca 1.99-x Zn 0.01 P2O7:Mn x The stress luminescent material is combined with polydimethylsiloxane (PDMS) to form an elastic film: first, the fluorescent material, PDMS and curing agent are mixed in a ratio of 1:1:0.1, and then the mixed slurry is poured into a pre-cleaned mold, and finally it is placed in a vacuum oven and cured at 80°C for 2 hours to obtain an elastomer containing stress luminescent material. Fig.18 Contains Ca 1.976 Zn 0.01 P2O7:Mn 0.014 The luminescence photo of the elastomer of fluorescent material under extrusion stress shows that the emission of green light can be clearly observed. The linear relationship between stress luminescence and mechanical force is as follows Fig.19 As shown, the self-healing characteristics are as follows Fig. 20 shown.
[0072] Embodiment 5
[0073] Weigh various raw materials CaCO3, MgCO3, (NH4)2HPO4, and Sm2O3 according to the chemical formula. NH4Cl is added as a flux at 4% of the mass of all raw materials, and the molar number of Sm2O3 weighed is 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, and 0.01, that is, the x value is 0.008, 0.01, 0.012, 0.014, 0.016, 0.018, and 0.02. After the above raw materials are fully ball-milled and mixed evenly, they are loaded into a corundum crucible, heated to 500°C at a heating rate of 5-10°C / min, and kept at 500°C for 1 hour in an air atmosphere. The temperature is raised to 1100°C and kept for 8 hours. After the sintered body is cooled, it is crushed, sieved, and classified to obtain the chemical composition of Ca in the present invention. 1.99-x Mg 0.01 P2O7:Sm x The stress luminescent material. 1.98 Mg 0.01 P2O7:Sm 0.01 The X-ray diffraction spectrum of Figure 1 The emission spectrum is shown in Fig.21 As shown in the figure, the strongest emission wavelength is at 595 nm of orange-red light. The stress luminescence of the powder during the grinding process is shown in the figure. Fig. 22 shown.
[0074] In this example, Ca 1.99-x Mg 0.01 P2O7:Sm x The stress luminescent material is combined with polydimethylsiloxane (PDMS) to form an elastic film: first, the fluorescent material, PDMS and curing agent are mixed in a ratio of 1:1:0.1, and then the mixed slurry is poured into a pre-cleaned mold, and finally it is placed in a vacuum oven and cured at 80°C for 2 hours to obtain an elastomer containing stress luminescent material. Fig.23 Contains Ca 1.98 Mg 0.01 P2O7:Sm 0.01 The luminescence photo of the elastomer of fluorescent material under extrusion stress shows that the emission of green light can be clearly observed. The linear relationship between stress luminescence and mechanical force is as follows Fig.24 As shown, the self-healing characteristics are as follows Fig.25 shown.
[0075] Embodiment 6
[0076] Weigh various raw materials CaCO3, SrCO3 according to the chemical formula, add NH4Cl as a flux at 5% of the weight of all raw materials, NH4H2PO4, Bi2O3. The weighed molar number of Bi2O3 is 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, that is, the x value is 0.008, 0.01, 0.012, 0.014, 0.016, 0.018, 0.02. After the above raw materials are fully ball-milled and mixed evenly, they are loaded into a corundum crucible, heated to 500°C at a heating rate of 5-10°C / min, kept at 500°C for 1 hour in an air atmosphere, and then raised to 1100°C and kept for 8 hours. After cooling the sintered body, it is crushed, sieved, and classified to obtain the chemical composition of Ca in the present invention. 1.99-x Sr 0.01 P2O7:Bi x Stress luminescent materials. Among them, Ca 1.976 Sr 0.01 P2O7:Bi 0.014 The X-ray diffraction spectrum of Figure 1 The emission spectrum is shown in Fig.26 As shown in the figure, the strongest emission wavelength is at 566 nm in yellow light. The stress luminescence of the powder during the grinding process is shown in the figure. Fig. 27 shown.
[0077] In this example, Ca 1.99-x Sr 0.01 P2O7:Bi x The stress luminescent material is combined with polydimethylsiloxane (PDMS) to form an elastic film: first, the fluorescent material, PDMS and curing agent are mixed in a ratio of 1:1:0.1, and then the mixed slurry is poured into a pre-cleaned mold, and finally it is placed in a vacuum oven and cured at 80°C for 2 hours to obtain an elastomer containing stress luminescent material. Fig.28 Contains Ca 1.976 Sr 0.01 P2O7:Bi 0.014 The luminescence photo of the elastomer of fluorescent material under extrusion stress shows that the emission of green light can be clearly observed. The linear relationship between stress luminescence and mechanical force is as follows Fig.29 As shown, the self-healing characteristics are as follows Fig.30 shown.
[0078] Comparative Example 1
[0079] Referring to Example 1, various raw materials CaCO3, (NH4)2HPO4, and Dy2O3 are weighed according to the chemical formula. The weighed molar numbers of Dy2O3 are 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, and 0.01, that is, the values of x are 0.008, 0.01, 0.012, 0.014, 0.016, 0.018, and 0.02. After the above raw materials are fully ball-milled and mixed evenly. After the above raw materials are fully ball-milled and mixed evenly, they are loaded into a corundum crucible, heated to 500°C at a heating rate of 5-10°C / min, kept at 500°C for 1 hour in an air atmosphere, and then the temperature is raised to 1300°C and kept for 8 hours. After the sintered body is cooled, it is crushed, sieved, and classified to obtain the chemical composition of Ca in the present invention. 2-x P2O7:Dy x Stress luminescent materials.
[0080] The difference between the comparative example and the embodiment 1 is that no flux is added in the comparative example 1, and there is no other difference. The powder obtained in the comparative example is tested by X-ray powder diffraction method, and the X-ray powder diffraction spectrum of the comparative example and the embodiment 3 is compared. Fig.31 As shown by Fig.31 It can be seen that when 2% of the flux NH4Cl is added to the raw materials, the peak intensity of the X-ray diffraction peak is more than twice that when it is not added, indicating that the preparation method of the present invention adds NH4Cl as a flux when preparing stress luminescent materials. The crystallization is better under the same crystal structure. The emission spectrum of the powder obtained in the comparative example and the embodiment 1 is as shown in Fig.32 As shown by Fig.32 It can be seen that when the flux is added at a ratio of 2% by mass to the raw material, the luminescence intensity of the fluorescent material is about 1.5 times stronger than when no flux is added, indicating that the addition of flux NH4Cl helps to increase the luminescence intensity of the fluorescent material.
[0081] It should be noted that: the above-mentioned luminescent materials include but are not limited to being combined with organic polymer elastic materials such as polydimethylsiloxane (PDMS) and PET to prepare various composite materials for application in specific mechanical visualization monitoring, electronic signature, intelligent wear, anti-counterfeiting, etc. In addition to the ammonium chloride used in the present invention, the flux can also use common fluxes such as boric acid. In the present invention, NH4Cl is preferably used as the flux, which can make the stress luminescent material crystallize well and have high luminescence intensity.
[0082] In summary, according to Figure 1It can be seen that the sample spectra prepared in the above embodiments are well formed, consistent in quality, and match the spectrum of the standard card. In addition, the luminescence intensity shown in the stress emission diagram in each embodiment is relatively high. The elastomer prepared by the luminescent material obtained according to each embodiment has a good linear relationship of force and good self-recovery characteristics, indicating that the surface material has application prospects in the fields of stress sensing. The self-recovering stress luminescence described in the present invention can achieve multiple emission bands in the visible light range, high stress luminescence intensity, and stable chemical properties. The manufacturing method is simple, pollution-free, easy to operate, low in cost, and suitable for large-scale industrial production. The multi-band self-recovering stress luminescent material of the present invention and the corresponding application composite material can have application prospects in mechanical visualization monitoring, electronic signature, intelligent wear, anti-counterfeiting and other aspects.
[0083] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a multi-band self-recovering stress luminescent material, characterized in that: The chemical expression of the multi-band self-recovery stress luminescent material is: a P2O7:R b , wherein M is at least one element selected from Mg, Ca, Sr, and Zn; P is phosphorus; O is oxygen; R is an element selected from Eu, Tb, Dy, Mn, Sm, and Bi; a and b are molar coefficients, and 1.5≤a<2, 0.001≤b≤0.5, and a+b=2; The preparation method of the multi-band self-recovering stress luminescent material comprises: (1) High-purity carbonate and / or acetate and / or oxide containing M, ammonium hydrogen phosphate or ammonium dihydrogen phosphate, and oxide and / or boride and / or carbonate containing R are used as raw materials, and flux is added, and the mixture is ground uniformly; (2) calcining the mixture obtained in step (1) at a high temperature in air or N2 / H2 atmosphere, wherein the calcination conditions are: heating to 500°C at a heating rate of 5-10°C / min and keeping the temperature for 1-2 hours, then heating to 1100-1300°C and calcining for 6-20 hours, and calcining at least once; the flux is ammonium chloride, and the flux accounts for 0.1%-5% of the total mass of the raw materials; (3) The calcined product obtained in step (2) is cooled, crushed and sieved to obtain the self-recovering stress luminescent material.
2. The method for preparing the multi-band self-recovering stress luminescent material according to claim 1, characterized in that: The chemical expression of the restorable stress luminescent material is Ca 1.984 P2O7:Dy 0.016 , the strongest emission wavelength is at 570 nm in yellow light.
3. The method for preparing the multi-band self-recovering stress luminescent material according to claim 1, characterized in that: The chemical expression of the restorable stress luminescent material is Ca 1.988 P2O7:Eu 0.012 , the strongest emission wavelengths are at 414 nm for blue light and 612 nm for red light.
4. The method for preparing the multi-band self-recovering stress luminescent material according to claim 1, characterized in that: The chemical expression of the restorable stress luminescent material is Ca 1.988 P2O7:Tb 0.012 , the strongest emission wavelength is at 541 nm in green light.
5. The method for preparing the multi-band self-recovering stress luminescent material according to claim 1, characterized in that: The chemical expression of the restorable stress luminescent material is Ca 1.976 Zn 0.01 P2O7:Mn 0.014 , the strongest emission wavelength is at 566 nm in yellow light.
6. The method for preparing the multi-band self-recovering stress luminescent material according to claim 1, characterized in that: The chemical expression of the restorable stress luminescent material is Ca 1.98 Mg 0.01 P2O7:Sm 0.01 , the strongest emission wavelength is at 595 nm of orange-red light.
7. The method for preparing the multi-band self-recovering stress luminescent material according to claim 1, characterized in that: The chemical expression of the restorable stress luminescent material is Ca 1.976 Sr 0.01 P2O7:Bi 0.014 , the strongest emission wavelength is at 566 nm in yellow light.
Citation Information
Patent Citations
High brightness mechanical luminescent material and preparation method thereof
CN102250614A